Determinants of the possibilities by investors' risk-taking: Empirical evidence from Vietnam - Linh Duy Bui; Trung Chi Le; Anh Huynh Ngoc Quang; Wing Keung Wong (Cogent Economics & Finance, 2021)
This paper focuses on determining the factors influencing investors' risk-taking through empirical evidence from Vietnam. This study investigates risk perception, expected return and herding behavior, and other determinants such as historical volatility and subjective financial risk attitude; according to previous studies, these are the main components affecting risk-taking behavior among investors. Overconfidence (better than average, miscalibration, and excessive optimism) is also taken into consideration. We employ pooled-OLS and quantile regression to overcome the shortage of research models in this field. In addition, we demonstrate how risk-taking behavior can be affected by those factors with the application of measures across four different investment channels. This study suggests implications for investors who wish to control risk.
Keywords: D01; D03; G02; 330; herding; overconfidence; Risk perception; risk preference; risk-taking